Juozas Kėkštas’s Cultural Mediation: The Interplay of Journalism, Translation, and Original Creative Work - Valčiukienė, Erika (Colloquia, 2026)
The article analyzes the cultural mediation of Juozas Kėkštas (1915–1981), who was involved with the circles of interwar Vilnius writers and later, the Žemininkai poets. The author of the article argues that Kėkštas’s place in the history of Lithuanian culture, commonly viewed as a “borderland poet,” is best brought to light when all areas of his literary activity – publishing, translations, and original poetry, as well as his publishing strategies – are seen and evaluated as one creative space. It is from this perspective that the interaction between different areas, the significance of specific authors Kėkštas translated, the consistency of his own work, and place in Lithuanian culture are best heightened. The research has shown that for Kėkštas, translation was not a secondary or incidental activity but an essential part of his creative stance, allowing him not only to articulate aesthetic and ideological positions more clearly, but also to intentionally shape the selection of texts, their interpretation, and the horizon of their reception. Kėkštas emerges as an active cultural and intercultural mediator, who linked different literary spaces, while simultaneously forming symbolic and social communities based not on territorial or political grounds, but rather on a shared experience of a catastrophic era, existential attitudes, and loyalty to creative and cultural work. The figure of Czesław Miłosz is particularly visible in this process, as his poetry translations link different periods and contexts of Kėkštas’s agency.